SCREENING OF SECONDARY METABOLITE-PRODUCING BACTERIA ASSOCIATED WITH CORALS USING 16S rDNA-BASED APPROACH - Ocky Karna Radjasa; Agus Sabdono (JOURNAL OF COASTAL DEVELOPMENT, 2003)
A total of 42 coral-associated bacteria were screened for their ability to produce secondary metabolites by using 16S rDNA-based approach. A specific oligonucleotides primer was used to amplify DNA non-ribosomal peptide synthetase (NRPS). Five strains were found to carry the NRPS gene and successfully inhibit the growth of other coral-associated and pathogenic bacteria. The phylogenetic characterization revealed that four strains belonged to currently known species Pseudoalteromonas luteoviolacea, Vibrio tubiashi, Vibrio carchiariae and Bacillus iodinum. On the other hand, one strain was apparently closely related with an unknown group of the gamma Proteobacteria, which was only recognized as uncultured clone 141H2.